Concrete imputation reasonable approach to the truth - Mendoza Ayma, Francisco Celis (2011)
In order to attain a reasonable belief of the truth as an assumption of a constitutionalized legal proceeding, the action must be based on specific charges that will rule out any attempt to rule on the basis of intuition alone, grounded on mere suspicion, that denaturalizes the cognitive quality of the criminal proceeding; with a view to building a program to harness the punitive power based on a specific accusation. To this effect, the accusation requires a number of factual elements structured according to their legal qualification, based on elements of certainty which will result in a specific accusation that will enable a person to exercise the right of defense, generating an adversarial proceeding, thereby configuring the very essence of the proceeding.